Effects of weathering and slope stability of Chai Wan Area, Hong Kong - Posit Nippitawasin; Prinya Nutalaya; Brand, E.W.; Onodera, T. F.; Government of Federal Republic of German (Bangkok : Asian Institute of Technology, 1978)
The Chai Wan area situated at the Northeast part of Hong Kong island and occupied area about 6.40 square kilometers. Two types of volcanic and a granite were found underlying landslide and colluvial deposits which formed the majority of the slope material. Schmidt rebound hardness test, penetration test, infiltration test and seismic survey were used to access the weathering effect of these rock types in the field in addition to the determinations of some physico-mechanical properties in laboratory. Test results indicated the decrease in the strength properties especially in shear strength characteristics with increased weathering. The test results were used in stability analysis and it was concluded that slope was stable on the rock material weathered to grade WI! but the stability was influenced by the variation of shear strength parameters; unit weight and water table condition on the material weathered to grade WIII and higher. A scheme of weathering grade classification. was proposed.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Sc.) - Asian Institute of Technology, 1978
Keywords: Weathering -- Hongkong -- Chai Wan Area; Rock slopes -- Hongkong -- Chai Wan Area